Factors of uneven growth of oil palm seedlings in between two nurseries at Bukit Gambir, Johor / Nurul Haliza Mohd Razali - Mohd Razali, Nurul Haliza (Faculty of Plantation and Agrotechnology, 2019)
Oil palm is a commodity crop that important to the country as a major contributor to the national income. By looking to the issues, it is really important to ensure that the oil palm that being marketed is having a quality and in a good condition. The objective of this study is to determine the possible factors of uneven growth of oil palm seedling; lack of nutrient, poor soil management, poor fertilizer management, and other possible factor. Besides, the materials uses in this research are the oil palm seedlings that come from two types of nurseries, while the methods uses are soil chemical analysis method and plant physical and chemical analysis method. The parts of the plants are taken and the analysis is being carried out. In this cases, plant heights is the main parameter that being taken in order to measure the performance of the seedling. The result of this research showing that there is no significant difference in between the two nurseries that located nearby.